The Role of Augmented Reality in Shaping Consumer Behavior - Ernestivita, Gesty (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the impact of Augmented Reality (AR) on consumer experiences in various retail contexts through a systematic literature review approach. By summarizing findings from a number of related studies, this research aims to understand how AR influences consumer immersion, satisfaction and loyalty levels, both in physical stores and e-commerce platforms. The research method involves analysis of relevant academic literature from various international databases such as Scopus, Web of Science, and Google Scholar. The results of the discussion show that AR has a significant impact on consumer experience, by increasing the level of immersion, satisfaction and loyalty. The implications of this research underscore the importance of using AR in increasing consumer engagement and loyalty in the retail sector, while also stating the need for further research to explore AR applications in the context of retail and consumer behavior.